KEPATUHAN MINUM OBAT PADA PENDERITA DM TIPE II - Deomedes; Rahmawati, Annisa; Pradika, Jaka (Literasi Intelektual, 2025)
Background: Diabetes Mellitus (DM) is a chronic disease that requires long-term management, including medication adherence, to prevent complications. However, medication adherence among DM patients remains low in various regions. Objective: To describe the level of medication adherence among patients with Type II Diabetes Mellitus in the working area of Manis Mata Health Center, Ketapang. Methods: This descriptive study used a total sampling technique involving 70 respondents diagnosed with Type II DM. Data were collected using the Morisky Medication Adherence Scale (MMAS-8) questionnaire and analyzed univariately to obtain the frequency distribution of respondent characteristics and adherence levels. Results: Most respondents were aged 56–66 years (45.7%), female (58.6%), had a junior high school education (40.0%), were unemployed (37.1%), and had suffered from DM for more than 5 years (70.0%). The level of medication adherence was very low, with 94.3% of respondents being non-adherent, 5.7% moderately adherent, and 0% fully adherent. Advanced age, low education, unemployment, and longer duration of illness were the main contributing factors to poor adherence. Conclusion: Medication adherence among patients with Type II DM in this study area was very low. Comprehensive interventions, continuous health education, family support, and optimization of non communicable disease control programs at the primary care level are essential to improve patient adherence.